Significances of daily disposable contact lenses during COVID-19 - Bhattarai, Sanjeev (Journal of Chitwan Medical College, 2021)
Contact lens is one of the preferred modes of refractive correction for children and adults. With proper care and maintenance, even during pandemic of COVID-19, contact lenses can be prescribed and worn by the patients without much fear of Coronavirus infection. Till now there is no strong clinical evidence that proves contact lenses are not safe to wear during COVID-19. But considering patient’s health and hygiene, various literatures have suggested that with compared to conventional or yearly disposable contact lenses, daily disposable contact lenses are safer to use during COVID-19. Since the daily disposable lenses are discarded daily after use at the end of the day, there is no need of extra care regarding manual cleaning and maintenance. Daily disposable lenses may have a very less or even no deposits and debris so makes patient more comfortable all over the time with less risk of Coronavirus infection.